Human papillomavirus E7 protein detection as a method of triage to colposcopy of HPV positive women, in comparison to genotyping and cytology. Final results of the PIPAVIR study. Issue 3 (15th May 2017) - Agorastos, Theodoros; Chatzistamatiou, Kimon; Moysiadis, Theodoros; Kaufmann, Andreas M.; Skenderi, Alkmini; Lekka, Irini; Koch, Isabel; Soutschek, Erwin; Boecher, Oliver; Kilintzis, Vasilis; Angelidou, Stamatia; Katsiki, Evangelia; et al.
Abstract : The objective of the presented cross‐sectional‐evaluation‐screening study is the clinical evaluation of high‐risk(hr)HPVE7‐protein detection as a triage method to colposcopy for hrHPV‐positive women, using a newly developed sandwich‐ELISA‐assay. Between 2013‐2015, 2424 women, 30‐60 years old, were recruited at the Hippokratio Hospital, Thessaloniki/Greece and the Im Mare Klinikum, Kiel/Germany, and provided a cervical sample used for Liquid Based Cytology, HPV DNA genotyping, and E7 detection using five different E7‐assays: " recom Well HPV16/18/45KJhigh", " recom Well HPV16/18/45KJlow", " recom Well HPV39/51/56/59", " recom Well HPV16/31/33/35/52/58" and " recom Well HPVHRscreen" (for 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59 E7), corresponding to different combinations of hrHPVE7‐proteins. Among 1473 women with eligible samples, those positive for cytology (ASCUS+ 7.2%), and/or hrHPV DNA (19.1%) were referred for colposcopy. Cervical Intraepithelial Neoplasia grade 2 or worse (CIN2+) was detected in 27 women (1.8%). For HPV16/18‐positive women with no triage, sensitivity, positive predictive value (PPV) and the number of colposcopies needed to detect one case of CIN2+ were 100.0%, 11.11% and 9.0 respectively. The respective values for E7‐testing as a triage method to colposcopy ranged from 75.0‐100.0%, 16.86‐26.08% and 3.83‐5.93. Sensitivity and PPV for cytology as triage for hrHPV(non16/18)‐positive women were 45.45% and 27.77%; for E7 test the respective values ranged from 72.72‐100.0% and 16.32‐25.0%. Triage of HPV 16/18‐positive women to colposcopy with the E7 test presents better performance than no triage, decreasing the number of colposcopies needed to detect one CIN2+. In addition, triage of hrHPV(non16/18)‐positive women with E7 test presents better sensitivity and slightly worse PPV than cytology, a fact that advocates for a full molecular screening approach. Abstract : What's new? HPV testing is not a complete cervical cancer screening: it identifies not the presence of disease, but an increased cancer risk. Not all women who test positive for high risk HPV really need colposcopy, but which ones do? These authors tested a new assay for an HPV oncoprotein, E7, which spurs cell transformation. They successfully showed that the assay could detect increased amounts of E7 and using this as the basis for further testing, they reduced the number of colposcopies ordered without missing any CIN2+ cases. Thus, this assay could be a useful partner to HPV testing for cervical cancer screening.